Arima Modeling for High-Frequency Channel Response in Equatorial Region - Jaya, Indra; Nawawi, Muhammad; Handoko, Lukman; Alfiah, Agry (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
Indonesia, an archipelagic country located along the equator, is highly vulnerable to natural disasters. At the same time, its geographical conditions require reliable telecommunications to strengthen connectivity across its many islands. One effective solution is the utilization of High-Frequency (HF) communication technology, which enables long-distance communication and supports broadcasting-based telecommunications. This approach can expand available frequency channels, making HF radio communication an important tool for disaster-prone regions like Indonesia. To optimize HF communication, researchers have developed various models of HF channel radio systems, often represented statistically and implemented through channel simulators. Among these approaches, the Auto Regressive Integrated Moving Average (ARIMA) model has been identified as particularly suitable. This is because ARIMA can handle the non-stationary characteristics of time-series data, such as those found in HF channel attenuation measurements. In the modeling process, several ARIMA configurations were tested, including ARIMA (0,1,1), (0,0,5), (1,0,0), (1,0,1), (1,0,2), and (0,0,4). From these options, two models—ARIMA (1,0,0) and ARIMA (1,0,2)—showed the closest fit to the observed data. The final selection was made using the Akaike Information Criterion (AIC), where the ARIMA (1,0,2) model emerged as the best. This model provides the most accurate representation for predicting HF channel attenuation, supporting more reliable telecommunications systems for Indonesia.